PRAGMALINGUISTICS: EXPLORING THE SOCIAL DYNAMICS OF LANGUAGE USE - Yulchiyeva Dilfuzaxon Zafarjon qizi (Journals Park Publishing, 2024)
This article provides a comprehensive overview of pragmalinguistics, a subfield of linguistics that explores the intricate relationship between language and social context. The author delves into key concepts within pragmatics, such as speech acts, politeness strategies, and conversational implicature, elucidating how language is used to convey meaning beyond literal interpretation. The practical implications of pragmalinguistics in language teaching, cross-cultural communication, and discourse analysis are discussed, highlighting its relevance in enhancing communicative competence and navigating diverse linguistic landscapes. The article also touches upon current research trends in pragmalinguistics, underscoring the evolving nature of language use in society. Overall, this insightful piece offers valuable insights into the social dynamics of language and the role of pragmatics in shaping effective communication strategies.
Keywords: Pragmalinguistics, linguistics, cross-cultural, pragmatic